Reverse logistics in retail: barriers and motivation to products and packaging return - Demajorovic, Jacques; Campos, Laida da Silva Oliveira; Campos, Juliana bonomi Santos de (Revista de Administração da UFSM, 2019)
The objective of this research is to analyze the development of the relationships between the internal areas of a retail company, its suppliers and customers involved in the management of reverse logistics (RL) in two contexts: product return and return packaging used in moving product logistics. A single case study with two units of analysis was conducted in one of the leading supermarket retailers in Brazil to answer the research questions. The results show that there are conflicts between the external actors, i.e. suppliers, producers and partners, and within the focal firms, between the commercial and logistics departments. The lack of objective alignment between the actors and the perception that RL is a cost-generating process undermines the effectiveness of the reverse flows of products and packaging in retail. It was observed; however, that a more collaborative relationship, driven by voluntary action and not by legislation, resulted in economic and environmental benefits for the retailer, indicating the potential intra and interdepartmental has to enable the management of reverse logistics in retail.